2006
DOI: 10.3366/afr.2006.0033
|View full text |Cite
|
Sign up to set email alerts
|

Race, Identity and Citizenship in Black Africa: The Case of the Lebanese in Ghana

Abstract: As we approach the post-colonial half century, transnationalism has become a major reality in Africa and the wider world with the proliferation of immigrants, refugees and displaced persons. But transnationalism is not a new development, and diaspora and globalization – both historical processes – have long served as contexts for the remaking of identity, citizenship and polity. Today, concepts such as ‘cosmopolitanism’ and ‘flexible citizenship’ are in vogue in a globalized world, as transnationalism challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…The recent and ongoing influx of Chinese merchants to Ghana and Senegal has intensified negative attitudes toward them on the part of local traders, including from naturalised, long-term residents, such as Lebanese traders, who have been present in West Africa since at least the beginning of the last century (Akyeampong 2006;Garlick 1960;Looß 1999;408 L. Marfaing and A. Thiel O'Brian 1975;Thioub 2009). 6 This hostility centres around a set of issues that differ only marginally between our two country cases, with the core grievance being strikingly similar: the encroachment of Chinese merchants on the local market, and the subsequent endangering of indigenous businesses and livelihoods.…”
Section: Tales Of Chinese Business and Commoditiesmentioning
confidence: 96%
“…The recent and ongoing influx of Chinese merchants to Ghana and Senegal has intensified negative attitudes toward them on the part of local traders, including from naturalised, long-term residents, such as Lebanese traders, who have been present in West Africa since at least the beginning of the last century (Akyeampong 2006;Garlick 1960;Looß 1999;408 L. Marfaing and A. Thiel O'Brian 1975;Thioub 2009). 6 This hostility centres around a set of issues that differ only marginally between our two country cases, with the core grievance being strikingly similar: the encroachment of Chinese merchants on the local market, and the subsequent endangering of indigenous businesses and livelihoods.…”
Section: Tales Of Chinese Business and Commoditiesmentioning
confidence: 96%
“…The majority of Lebanese moved to the U.S. and Latin America, in particular Brazil (Winder, 1962), while a much smaller, but significant group migrated to (West) Africa. 8 Most scholars (Akyeampong, 2006;Bierwirth, 1999;Obi, 2008;Winder, 1962) concluded that Lebanese migrants' preferred destination was the U.S., and their arrival in (West) Africa can be traced to a number of factors; it was considerably cheaper and easier in that there were no or few hurdles (e.g., health requirements, immigration controls) to overcome (Obi, 2008;Winder, 1962). Winder (1962) also suggested that some Lebanese migrants ended up in West Africa due to "unscrupulous Marseilles shipping agent[s]" (p. 297) who put the hopeful future Americans instead on a ship to a coastal city in West Africa rather than to New York or São Paulo (see also, Leighton, 1979).…”
Section: Lebanese Migration To Liberiamentioning
confidence: 99%
“…Winder (1962) also suggested that some Lebanese migrants ended up in West Africa due to "unscrupulous Marseilles shipping agent[s]" (p. 297) who put the hopeful future Americans instead on a ship to a coastal city in West Africa rather than to New York or São Paulo (see also, Leighton, 1979). The vast majority of Lebanese migrants to West Africa were of lower socioeconomic status and did not have a lot of (monetary) wealth (Akyeampong, 2006;Beydoun, 2013).…”
Section: Lebanese Migration To Liberiamentioning
confidence: 99%
See 2 more Smart Citations